Partitioning of Antioxidants in Edible Oil-Water Binary Systems and in Oil-in-Water Emulsions - Sonia Losada-Barreiro; Fátima Paiva-Martins; Carlos Bravo-Díaz (MDPI AG, 2023)
In recent years, partitioning of antioxidants in oil-water two-phase systems has received great interest because of their potential in the downstream processing of biomolecules, their benefits in health, and because partition constant values between water and model organic solvents are closely related to important biological and pharmaceutical properties such as bioavailability, passive transport, membrane permeability, and metabolism. Partitioning is also of general interest in the oil industry. Edible oils such as olive oil contain a variety of bioactive components that, depending on their partition constants, end up in an aqueous phase when extracted from olive fruits. Frequently, waste waters are subsequently discarded, but their recovery would allow for obtaining extracts with antioxidant and/or biological activities, adding commercial value to the wastes and, at the same time, would allow for minimizing environmental risks. Thus, given the importance of partitioning antioxidants, in this manuscript, we review the background theory necessary to derive the relevant equations necessary to describe, quantitatively, the partitioning of antioxidants (and, in general, other drugs) and the common methods for determining their partition constants in both binary (PWOIL) and multiphasic systems composed with edible oils. We also include some discussion on the usefulness (or not) of extrapolating the widely employed octanol-water partition constant (PWOCT) values to predict PWOIL values as well as on the effects of acidity and temperature on their distributions. Finally, there is a brief section discussing the importance of partitioning in lipidic oil-in-water emulsions, where two partition constants, that between the oil-interfacial, POI, and that between aqueous-interfacial, PwI, regions, which are needed to describe the partitioning of antioxidants, and whose values cannot be predicted from the PWOIL or the PWOCT ones.